Sleep Quality and Sleep Disturbances among Breast Cancer Patients Attending a Tertiary Cancer Center in Nepal: A Descriptive Cross-sectional Study - Kandel, Bibek; Tiwari, Sagar; Jha, Jay Bhushan; Thapaliya, Prechan; Sah, Guru Sharan (Nepalese Journal of Cancer, 2026)
Introduction: Sleep problems are common in people with cancer and can affect quality of life. This study aimed to find the prevalence of poor sleep quality and describe common sleep disturbances among breast cancer patients attending a tertiary cancer care center in Nepal. Methods: This descriptive cross-sectional study was conducted at B. P. Koirala Memorial Cancer Hospital (BPKMCH), Nepal, from July 2025 to December 2025. A non-probability convenient sampling method was used to recruit 391 breast cancer patients attending inpatient and outpatient services. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data was entered in Microsoft Excel 2016 and analyzed using STATA version 17. Results: Among 391 participants, the prevalence of poor sleep quality (PSQI global score >5) was 92 (23.53%). The mean global PSQI score was 4.82±3.12. Difficulty initiating sleep at least once per week was reported by 115 (29.41%) participants, and 156 (39.90%) reported waking in the middle of the night at least once per week. A total of 92 (23.53%) participants reported using sleep medication at least once per week. Conclusion: About one-fourth of breast cancer patients had poor sleep quality by PSQI. Many others reported specific sleep problems, suggesting that sleep issues may be present even when overall sleep is not described as very poor. Routine screening and simple supportive measures may help improve patient well-being.